Digital devices in the governing of the European Education Space: The case of SORPRENDO software for career guidance. (May 2020) - Romito, Marco; Gonçalves, Catarina; De Feo, Antonietta
In this paper, we discuss the case of the recent introduction of a career guidance software within Italian schools with the aim to explore the use of digital devices in the governance of educational processes within the field of lifelong guidance. First, we provide a semiotic analysis of the software and its online platform with the aim of exploring how it articulates a complex network of material and discursive relations. Second, we show the types of practices the software makes 'affordable' within the Italian school context, and the organisational and cultural tensions it creates. Following recent studies on digital governance and adopting a policy instrument approach, we show how the introduction of a digital object within the school environment mobilises school actors around new ways of conceiving and delivering education that transcends the local dimension (looking towards national and European ideas) and favours the penetration of economic imperatives and rationales within Italian schools. The career guidance software analysed constitutes in this regard a meaningful illustration of how the governance of the European education space is mediated, activated and accomplished using digital instruments. Software, platforms and websites exert a persuasive power on their users, who in turn contribute to transform the educational order while transforming themselves.